Microstructure, Mechanical Properties, And Corrosion Behavior Of Cryorolled Low Carbon Steel Subjected To Heat Treatment - Motham, Kanchana (2018)
Low carbon steel has been extensively used in various industries, but its limited strength restricted the potential development in applications. In recent years, ultrafine grained (UFG) structural materials have been studied, because they are expected to provide superior mechanical properties. The present works aim at producing UFG in low carbon steel using cryorolling and investigated its effect on heat treatment and thickness reduction on microstructure, mechanical properties and corrosion behavior. The details of microstructural characteristics and mechanical properties of low carbon steel were investigated using optical microscope (OM), scanning electron microscope (SEM), electron back scattered diffraction (EBSD), X-ray diffraction (XRD), Vickers microhardness and tensile test. Low carbon steel underwent pre-annealing at 550°C, 750°C, and 900°C at 15, 30, 60 and 120 minutes followed by cryorolling. Sample treated at 550°C (60 minutes) shows the optimum properties and was chosen for futher investigation on different thickness reduction; 50%, 60%, 70%, 80% and 90%. The highest hardness and tensile strength attained at 90% reduction with the values of 208.5 Hv and 826.5 MPa respectively which result in the smallest crystallite size (38.16 nm) and highest lattice strain (20.58 x 10-4). Corrosion resistance decreases with thickness reduction. Post-annealed at 450°C shows recrystallization state for 90% reduction and achieved ultrafine grain with hardness and tensile strength of 157.9 Hv and 587.7 MPa respectively.